Analysis of Wanggu River Sedimentation Due to Land Cover Change using ArcSWAT and its Alternative Control - Hariyanto, Andri Kwin; Sisinggih, Dian; Andawayanti, Ussy (Fakultas Teknik Universitas Brawijaya, 2024)
The downstream Wanggu watershed is located in Kendari City, the capital of Southeast Sulawesi Province, with an area of 329.59 km2. So it is very important to arrange the right space. In this research, an analysis of the impact of changes in land cover on sedimentation levels will be carried out, as a basis for considering space utilization so as not to exceed the carrying capacity of the watershed. The analysis method uses the Arcswat application, and land cover changes using comparative data for 2001, 2006, 2009, 2014, and 2020. One of the obstacles in land cover classification is the presence of clouds that cover part of the image. In this research, Google Earth Engine (GEE) is used which will automatically process historical data so that areas covered by clouds are replaced with images that are clear of clouds. The research results show that agricultural land cover has the greatest influence, and overall the watershed shows accumulated sedimentation of 2,515,409.90 tons or a rate of 76.40 tons/ha for land cover in 2001 and sedimentation of 2,808,683.45 tons or rate 85.31 tons/ha. for land cover in 2020.